Narrative Inquiry: The Use of Authentic Material in English Language Learning at Elementary School in Banyuwangi - Apriliani, Dita (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
This study aims to explore the experiences of students and teachers in using authentic materials in English language learning at elementary schools in Banyuwangi. Using a qualitative research design and a narrative inquiry approach, the study involved 15 fourth and fifth-grade students and two English teachers who have experience using authentic materials. The findings indicate that the use of authentic materials relevant to the local context significantly enhances students' motivation, language skills, and understanding of English. Students feel more connected to the material taught when it reflects their culture and daily life, such as articles about local tourist attractions and traditions. Although there are challenges in selecting materials that are appropriate for students' skill levels, this research emphasizes that authentic materials can make English language learning more contextual and meaningful. The results of this study provide important insights for the development of curricula and English teaching practices in Indonesia.